DIALEKTIKA HEGEL DAN KONFLIK KELAS MARX DALAM REKONSTRUKSI PEMBELAJARAN PAI - Fikri Ghopari; Meiza Fajar Akbar; Anam Khoirul Rozak; Juniari Tri Trisno (Yayasan Pendidikan Literasi Borneo, 2025)
The phenomenon of social change and the complexity of contemporary knowledge dynamics demand a more reflective, critical, and contextual learning paradigm for Islamic Religious Education (IRE). Hegel's dialectic, which emphasizes the process of development through thesis–antithesis–synthesis, and Karl Marx's class conflict theory, which views history as an arena of struggle between the dominant and oppressed classes, provide an important philosophical framework for interpreting social and educational realities. This study aims to examine the basic concepts of Hegel's dialectic and Marx's class conflict theory and analyze their implications for the reconstruction of IRE learning. This study uses a qualitative approach with a library research method, utilizing primary and secondary sources in the form of works by Hegel and Marx, journal articles, and related academic literature. Data collection techniques were carried out through literature search, selection, and documentation, while data analysis used content analysis and dialectical comparative analysis through the process of identification, categorization, interpretation, and synthesis of concepts. The results show that Hegel's dialectic contributes to strengthening critical thinking skills in learning, while Marx's class conflict theory directs attention to social awareness and structural justice. Both can be reconstructed in PAI learning through a dialogical approach, problem-posing, strengthening critical awareness, and integrating emancipatory values, so that learning becomes more relevant, transformative, and responsive to social change.